Avoidance of mussel farms by dusky dolphins ( Lagenorhynchus obscurus ) in New Zealand - HC Pearson; RL Vaughn‐Hirshorn; M Srinivasan; B Würsig (New Zealand Journal of Marine and Freshwater Research, 2012)
We describe fine‐scale interactions between dusky dolphins and mussel farms in Admiralty Bay, New Zealand. We examined dusky dolphin presence in nearshore mussel farms, coordinated feeding behaviours in and near mussel farms, and long‐term changes in regional population abundance. Sampling methods included boat‐based surveys, focal follows, underwater observations, and photo‐identification. Correcting for area, dusky dolphins spent significantly less time inside mussel farms versus outside mussel farms and other nearshore areas (both P

Monitoring the state of New Zealand rivers: How the River Values Assessment System can help - KFD Hughey; KL Booth (New Zealand Journal of Marine and Freshwater Research, 2012)
The River Values Assessment System (RiVAS) is a standardised multi‐criteria analysis approach for developing river rankings for diverse values (e.g. irrigation, whitewater kayaking, native birds) to aid decision‐making regarding various aspects of river management. The method identifies primary attributes that characterise the value and an indicator for each. Eleven values have been, or are being, implemented. In this paper, the distribution of primary attributes and indicators by value are mapped. Almost all values require some sort of ‘count’ data (especially recreational and ecological values) and most require water quantity or water quality data. Conversely, some values require data solely pertinent to that value. The tangata whenua (indigenous peoples of New Zealand) value is the most holistic. Findings suggest that comprehensive state of the environment reporting for rivers requires data additional to that currently collected, especially recreation‐related data. RiVAS provides a useful framework for thinking strategically about monitoring and reporting.

The population genetic structure of the waratah anemone ( Actinia tenebrosa ) around New Zealand - AJ Veale; SD Lavery (New Zealand Journal of Marine and Freshwater Research, 2012)
The genetic structure of populations is often shaped by the reproductive system and larval properties of the species. The waratah anemone ( Actinia tenebrosa ) reproduces through both asexual clones, which have very short‐distance dispersal, and sexual larvae, which are believed to disperse much greater distances. The impact of this mixed strategy on the New Zealand population structure of Actinia tenebrosa was investigated using microsatellite markers. The analysis incorporated 24 sampling locations from around New Zealand and one Australian location, using four microsatellite markers, n = 420. We observed low connectivity and high genetic differentiation between all locations sampled, with a distinct pattern of isolation by distance. The most distinct grouping of locations sampled was the north‐east of the North Island from Cape Reinga to East Cape, which was identified by SAMOVA and STRUCTURE analyses as being moderately diverged from the remainder of the country. A tentative correlation was observed between genetic clustering and biogeographic regionalisation, where the distribution of a number of genetic clusters matched previously defined biogeographic regions. Within each location sampled, large numbers of clones were present and a latitudinal cline was observed in the relative contribution of asexually and sexually generated recruits, with an increase in asexual recruits on the South Island's east coast.

Using climate downscaling to hypothesise impacts on apex predator marine ecosystem dynamics - M Srinivasan; HC Pearson; RL Vaughn‐Hirshorn; B Würsig; R Murtugudde (New Zealand Journal of Marine and Freshwater Research, 2012)
Climate downscaling studies help to connect global predictions and projections with regional dynamics and generate a better understanding of past and future conditions. Adding ecological variables and trophic relationships into the climate equation is challenging since there are few clear connections. The present study is an exploratory data analysis to explain dusky dolphin ( Lagenorhynchus obscurus ) encounter rate patterns in Admiralty Bay, New Zealand. During 2001–2006, dolphin encounter rate in winter decreased from 6 to 0.8 groups/h and the proportion of dolphin groups observed feeding decreased from 80% to 38% in Inner Admiralty Bay. These trends generally corresponded to cooler and moderate El Niño Southern Oscillation years, lower sea surface height, southwesterly winds, increased surface mixing and decreased sea surface salinity. To fully grasp the significance of these relationships and potential impact(s) on dolphin population trends, directed long‐term studies that synthesise dolphin, prey, water quality, anthropogenic pressures and climatic information into regional climate‐ecosystem models are needed.

The black petrel ( Procellaria parkinsoni ) in pelagic waters off northern Chile: a southern extension to the known distribution and interactions with the pelagic longline fishery - LA Cabezas; J Ruiz; O Yates; M Bernal (New Zealand Journal of Marine and Freshwater Research, 2012)
During seabird censuses performed as part of scientific research looking into seabird bycatch onboard industrial pelagic longline vessels targeting swordfish ( Xiphias gladius ) we made the first documented records of black petrel ( Procellaria parkinsoni ) in the pelagic waters of northern Chile, considerably extending the species’ range southward. These observations were made during hauling operations in the austral winters of 2008, 2009 and 2010 between 23°00'S and 32°49'S. Black petrels were observed in 9.6% of censuses and a total of 10 birds were recorded. Despite the fact that this species fed upon discards and wastes generated during fishing, no incidental mortality was observed. Our results are relevant to the conservation of the black petrel in the south‐eastern Pacific marine ecosystem, as they provide new information on species range and interactions with pelagic fisheries.

Editorial - Doug Mountfort (New Zealand Journal of Marine and Freshwater Research, 2012)

Editorial Board (New Zealand Journal of Marine and Freshwater Research, 2012)

Sixth national survey of pesticides in groundwater in New Zealand - ME Close; A Skinner (New Zealand Journal of Marine and Freshwater Research, 2012)
The 2010 4‐yearly national survey of pesticides in groundwater included 162 wells. The aims of the survey were to update the national overview of pesticides in New Zealand's groundwater systems, to investigate temporal variation in pesticide concentrations between surveys, and to identify environmental factors associated with pesticide contamination. Pesticides were detected in 38 wells (23%), with two or more pesticides detected in 15 wells (9%). Pesticides were measured in wells in nine of the 14 regions sampled. One well showed a dieldrin concentration greater than the maximum acceptable value for drinking water. A total of 22 different pesticides were detected. Herbicides were the most common pesticide group detected. Levels of only three of the 66 pesticide detections exceeded 1 mg/m 3 . Comparisons with earlier surveys indicate that a similar percentage of wells had detectable pesticides in the last four surveys once correction for variable detection limits was made.

The role of dams in altering freshwater fish communities in New Zealand - PG Jellyman; JS Harding (New Zealand Journal of Marine and Freshwater Research, 2012)
Dams are important structures for generating electricity and irrigation, but they often severely modify river hydrology and geomorphology and thus impact freshwater communities. These effects are broadly predictable and therefore, at a catchment scale, biological communities should respond in some predictable manner. We interrogated the New Zealand Freshwater Fish Database to determine whether dams have predictable catchment‐scale effects on fish assemblages. Seven selection criteria were applied to over 2000 dams, resulting in 30 dams being considered suitable for analysis. Comparisons were made above and below dams and with data from undammed sites which showed that community composition was significantly different above and below dams. Sites above dams had lower species richness, a lower percentage of diadromous species and a higher percentage of exotic species compared to below dams. None of these differences were present at undammed sites. In summary, dams restrict the movement of diadromous fish generally resulting in their reduction or loss from above‐dam habitats and also create artificial lentic ecosystems that exotic species can successively exploit. These changes to fish communities were found across New Zealand and should be viewed as a general consequence of any new dam construction unless fish management and conservation measures are undertaken.

The first report of Vulcanodinium rugosum (Dinophyceae) from the South China Sea with a focus on the life cycle - N Zeng; H Gu; KF Smith; LL Rhodes; AI Selwood; W Yang (New Zealand Journal of Marine and Freshwater Research, 2012)
An individual non‐motile (NM) cell was isolated from a surface sediment sample collected in Guangxi, China and subsequently established as a dinoflagellate strain in culture. The motile cells are 22.5–32.5 µm long and 20.0–30.0 µm wide, with a plate formula of Po, X, 4′, 3a, 7″, 6c, 5(?)s, 5″′, 2″″, fitting the description of Vulcanodinium rugosum . The Chinese strain shares 99.8%, 97.4% and 96.7% similarity (LSU sequence) with those from Australasia, France and Japan. Asexual division of V. rugosum takes place either in the thecate motile stage or within a NM division cell. Motile cells divided by binary fission inside the parent cell and transformed to NM division cells within 24 h. The NM cell underwent one to three consecutive divisions within the parent wall. The divisions were not always synchronous and neither was the release of motile cells from the NM cells. It generally took 4 to 6 days for the NM cells to complete one division. NM cells survived for 1 month at 4 °C in the dark, suggesting that they might play an important role in species dispersal. A novel pinnatoxin was detected at 20 pg cell −1 and no other known pinnatoxins (A–G) were detected.

Diet of rainbow trout in Lake Rotoiti: an energetic perspective - JM Blair; BJ Hicks; R Pitkethley; N Ling (New Zealand Journal of Marine and Freshwater Research, 2012)
We characterised seasonal and ontogenetic changes in diet and prey energy density of rainbow trout ( Oncorhynchus mykiss ) in Lake Rotoiti, New Zealand, to better understand the prey requirements of trout in central North Island lakes. Common smelt ( Retropinna retropinna ) was the dominant prey item of rainbow trout larger than 200 mm (77.8% of diet by weight), followed by kōura (freshwater crayfish Paranephrops planifrons ; 6.3%), common bully ( Gobiomorphus cotidianus ; 5.5%), and kōaro ( Galaxias brevipinnis ; 3.4%). Juvenile rainbow trout (

Distribution of backswimmers in shallow ponds of Patagonia and their predatory role on a common tadpole–copepod assemblage - FG Jara; MG Perotti; MC Diéguez (New Zealand Journal of Marine and Freshwater Research, 2012)
In this study, the distribution and occurrence of backswimmers in 21 fishless ponds was analysed in the Nahuel Huapi National Park (Patagonia, Argentina). We performed laboratory experiments to study the impact of different developmental stages of the endemic backswimmer Notonecta vereertbruggheni on typical co‐occurring prey. We recorded three species of backswimmers N . vereertbruggheni , Notonecta virescens and Notonecta fazi . A seasonal study in Fantasma pond showed that adults of N . vereertbruggheni colonise and reproduce in the pond in spring and summer, co‐occurring with other macroinvertebrates and endemic tadpoles. Predation experiments explored the impact of N . vereertbruggheni on two large co‐occurring prey, the calanoid copepod Parabroteas sarsi and the tadpoles of Pleurodema thaul . The backswimmer consumed more copepods than tadpoles when prey was offered separately. Selectivity experiments demonstrated that the copepods were preferred over the tadpoles. Backswimmers may impact the typical assemblages of organisms found in fishless ponds of Patagonia during spring and summer.

The spawning dynamics of snapper ( Chrysophrys auratus ) in northern Spencer Gulf, South Australia - Richard J Saunders; Anthony J Fowler; Bronwyn M Gillanders (New Zealand Journal of Marine and Freshwater Research, 2012)
This study investigated the inter‐ and intra‐annual variation in the spawning dynamics of snapper ( Chrysophrys auratus ). Reproductive samples from northern Spencer Gulf, South Australia were collected over three seasons (2005/06, 2006/07 and 2007/08) and were analysed macro and microscopically. Spawning activity was determined by calculating estimates of spawning fraction and batch fecundities. The onset of spawning occurred in November but varied between years and corresponded with times when water temperature was between 18 °C and 20 °C. The length of the spawning season also differed between years. In each year the peak spawning activity occurred during December when fish spawned almost daily. Spawning frequency and relative batch size did not differ between the first two spawning seasons but, in the third season, batch size was considerably greater and spawning fractionally lower. These results are contrasted with a known recruitment of 0+ over the three years of the study.

Open‐water integrated multi‐trophic aquaculture: environmental biomitigation and economic diversification of fed aquaculture by extractive aquaculture - Thierry Chopin; John Andrew Cooper; Gregor Reid; Stephen Cross; Christine Moore (Reviews in Aquaculture, 2012)
Integrated multi‐trophic aquaculture (IMTA) seeks to biodiversify fed aquaculture (e.g. finfish or shrimps) with extractive aquaculture, recapturing the inorganic (e.g. seaweeds) and organic (e.g. suspension‐ and deposit‐feeders) nutrients from fed aquaculture for their growth. The combination fed/extractive aquaculture aims to engineer food production systems providing both biomitigative services to the ecosystem and improved economic farm output through the co‐cultivation of complementary species. Major rethinking is needed regarding the definition of an ‘aquaculture farm’ and how it works within an ecosystem. The economic values of the environmental/societal services of extractive species should be recognized and accounted for in the evaluation of the full value of these IMTA components. Seaweeds and invertebrates produced in IMTA systems should be considered as candidates for nutrient/carbon trading credits. While organic loading from aquaculture has been associated with localized benthic impacts, there have also been occurrences of increased biodiversity and abundance of wild species in response to moderate nutrient enrichment and the use of infrastructures as substrates. To develop efficient food production systems, it will be important to understand and use the duality of nutrients (essential when limiting/polluting when in excess) to engineer systems producing them in moderation so that they can be partially recaptured while maintaining their concentrations optimal for healthy and productive ecosystems. Measures of species diversity, colonization rates, abundance, growth and ecosystem functions with respect to nutrient partitioning and recycling, species interactions and control of diseases could represent valid indicators for the development of robust performance metrics.

Environmental comparison of intensive and integrated agriculture–aquaculture systems for striped catfish production in the Mekong Delta, Vietnam, based on two existing case studies using life cycle assessment - Ingeborg N. Kluts; José Potting; Roel H. Bosma; Le T. Phong; Henk M. J. Udo (Reviews in Aquaculture, 2012)
Vietnam is the largest producer for the export of striped catfish. Traditionally striped catfish production in the Mekong Delta took place in integrated agriculture–aquaculture systems, but has shifted recently to intensive systems to meet increasing export demands. A recent study quantified the environmental impact of intensive striped catfish production in Vietnam. Another did the same for integrated systems. Both studies used life cycle assessment, covered similar environmental impact categories, and were roughly matched in the production stages included. However, an environmental comparison of both systems has not been made so far. The objective of this paper is to make a comparative life cycle assessment of striped catfish production in intensive and integrated systems. The comparison was based on existing life cycle assessments on these systems, but their methodological choices and data had to be aligned. The results show that striped catfish production in intensive systems contributes considerably more to seven of the nine assessed impact categories (global warming, ozone depletion, acidification, eutrophication, photochemical oxidation, human toxicity, freshwater ecotoxicity, marine aquatic ecotoxicity, fossil depletion). Only contributions to eutrophication and freshwater ecotoxicity were higher for the integrated systems than for the intensive systems. In both systems, grow‐out fish farming contributes most to eutrophication and freshwater ecotoxicity, whereas feed production contributes most to all other impact categories. The environmental performance of integrated striped catfish production is convincingly better in most impact categories. This raises questions about whether (elements of) these systems can be used to mitigate the environmental impact of intensive striped catfish production.

Chinese Abstracts (Reviews in Aquaculture, 2012)

Issue Information (Reviews in Aquaculture, 2012)

Megalocytivirus infection in fish - Kuttichantran Subramaniam; Mohamed Shariff; Abdul Rahman Omar; Mohd Hair‐Bejo (Reviews in Aquaculture, 2012)
Megalocytivirus is a newly discovered DNA‐virus from the Iridoviridae family that possesses icosahedral symmetry and has a size range of 140–200 nm diameter. Based on genetic differences, Megalocytivirus is divided into three major groups; infectious spleen and kidney necrosis virus which is reported to cause disease in numerous marine and freshwater fish species, red sea bream iridovirus that mainly infects red sea bream [ Pagrus major (Temminck & Schlegel 1843)] and turbot reddish body iridovirus that is reported to infect Asian flounder species. Megalocytivirus has not been studied as extensively as other genera in the Iridoviridae family until recently; these viruses have received the most attention in research due to the wider host range and cause significant mortality and economic losses in the aquaculture industry. This review provides information on taxonomy, viral properties, epizootic, pathology and diagnostics of Megalocytivirus infection in fish.

Is lower intensity aquaculture a valuable means of producing food? An evaluation of its effects on near‐shore and inland waters - James S. Diana (Reviews in Aquaculture, 2012)
The effects of aquaculture on the environment have been the subject of much examination, but most of the focus has been on shrimp and salmon. These are not the most common species grown in aquaculture, nor the most common systems used. About 60% of production today uses lower intensity culture to produce organisms in natural systems such as ponds. This paper is an overview of the positive and negative environmental impacts of lower intensity aquaculture. The ranked positive impacts of lower intensity aquaculture include: conservation aquaculture that supplements reproduction in natural populations; improving the quality of natural waters through filtering or consuming wastes by cultured organisms; reducing pressure on wild stocks by providing alternative sources in the market; and replacing damaging employment with more sustainable aquaculture jobs. Negative impacts include: escapement of alien species that become invasive; eutrophication of receiving waters from pond effluents; release of parasites and diseases into natural communities; escapement of unique genotypes resulting in genetic alteration of native stocks; land degradation due to pond construction; release of antibiotics or other drugs into receiving waters; depletion of natural resources such as water; loss of benthic biodiversity from settling of sediments; and reductions in natural populations by collection of larval or juvenile fish. Some impacts, especially the use of fishmeal and the transmission of disease, are much less common in lower intensity aquaculture systems. Aquaculture has an important role in current and future food production, and in many cases lower intensity aquaculture provides a sustainable solution to increased aquaculture production.

Distribution of southern right whales on the Auckland Islands calving grounds - W Rayment; A Davidson; S Dawson; E Slooten; T Webster (New Zealand Journal of Marine and Freshwater Research, 2012)
Southern right whales ( Eubalaena australis ) were virtually extirpated from New Zealand by commercial whaling, but are now recovering. Previous research at the Auckland Islands has suggested that Port Ross, a sheltered embayment at the northern end of the islands, is the primary calving ground for right whales in New Zealand. However, an abundance of potentially suitable calving areas exist outside Port Ross, raising the question of whether the growing population might be expanding its distribution to occupy new or former habitats. To address this we conducted the first systematic line‐transect survey of potential right whale calving habitat at the Auckland Islands in winter 2011. High densities of southern right whales were sighted inside Port Ross, including all but one of the 21 mother‐calf pairs recorded. The survey confirmed that Port Ross is the principal calving area for southern right whales in the Auckland Islands. This conclusion has implications for the estimation of demographic parameters of right whales in New Zealand, which have thus far relied on data gathered largely in Port Ross, and highlights the importance of protecting this habitat.

Land use influences on suspended sediment yields and event sediment dynamics within two headwater catchments, Waikato, New Zealand - AO Hughes; JM Quinn; LA McKergow (New Zealand Journal of Marine and Freshwater Research, 2012)
Information on the effect of human‐induced disturbances on sediment yields and sediment sources from New Zealand catchments is limited. This study analyses the sediment yields and event sediment dynamics for a 12‐year period from two paired headwater catchments within the Waikato region. One catchment (Whakakai) was entirely vegetated in native forest, while the other (Mangaotama) was of mixed land use. Near the beginning of the study period, an integrated catchment management plan was implemented with the Mangaotama catchment. This plan included riparian planting, planting of degraded land in Pinus radiata and changes in stock management. Long‐term in‐stream turbidity data was calibrated with suspended sediment concentration (SSC) measurements and used to determine event and annual sediment yields. Hysteresis of the discharge (Q)–SSC relationship during events was used to infer differences in sediment sources. Event sediment yields within the Mangaotama catchment were similar to Whakakai catchment during small events ( c . 1.01‐year return period). For larger and less frequent events (>5‐year return period), the event yields from Mangaotama exceeded Whakakai by about a factor of three, probably due to mass movement initiation. The specific sediment yield (±1σ) from Mangaotama (97±39 t/km 2 /year) was around 60% higher than Whakakai (60±22 t/km 2 /year). Clockwise hysteresis in the Q–SSC relationship dominated at Mangaotama, indicating the importance of near‐channel sources. The persistence of near‐channel source dominance throughout the study period (despite major land use changes) was attributed to switching of erosive mechanisms (i.e. from cattle‐induced mechanical disturbance to subaerial processes). The prevalence of anti‐clockwise hysteresis in the Q–SSC relationship of events at Whakakai suggests that hillslope sources are likely to be a principal source of eroded sediment. Such information provides valuable information that may help guide future decisions on the application of catchment rehabilitation measures.

Near‐surface water temperatures in Doubtful Sound and response to natural and anthropogenic drivers - E Goodwin; CD Cornelisen (New Zealand Journal of Marine and Freshwater Research, 2012)
New Zealand fiords frequently feature a buoyant low‐salinity layer (LSL) leading to unique biological communities on their rock walls. The LSL has previously been distinguished by its temperature, but we show this is not always reliable. We describe temporal and spatial patterns in water temperature in Doubtful Sound, and the influences of rainfall, wind, air temperature and the discharge from the Manapōuri hydroelectric power scheme. Surface (0.5 to 19 m depth) temperatures in the fiords varied considerably at frequencies corresponding with season and weather. Distinct weather events coincided with fluctuations in surface temperatures of 5 °C to 10 °C, a magnitude of temperature change comparable to seasonal variability. Variability of surface water temperatures declined with proximity to the hydroelectric discharge. Statistical analyses indicated that changes in climate and weather are likely to have a larger effect on temperatures than changes in the rate of freshwater discharge.

Facilitation of upstream passage for juveniles of a weakly swimming migratory galaxiid - K Doehring; RG Young; AR McIntosh (New Zealand Journal of Marine and Freshwater Research, 2012)
The mitigating effects of fish passes to aid fish dispersal are well recognised; however, non‐sports fish species, juveniles and weak swimmers have mostly been neglected when developing solutions to fish passage issues. We studied the juvenile (fork length, FL Galaxias maculatus ), up an artificial ramp to evaluate the effects of fish size, ramp slope (5°, 15°, 25°), water velocity and the potential need for resting opportunities (pools) for a successful ascent. Water velocity significantly increased and fish passage success significantly decreased with ramp angle, with only one fish passing the 25° ramp. On average, fish had to be 10 mm larger to ascend a 15° ramp angle than at 5°. Pools did not enhance passage success in this study. To facilitate fish passage at barriers for weakly swimming fish species like juvenile īnanga, ramps should provide a rough surface substrate and have an optimal angle of 5° for a 3‐m ramp.

Seasonal changes in the biochemical composition of Evechinus chloroticus gonads (Echinodermata: Echinoidea) - W Verachia; MA Sewell; B Niven; M Leus; MF Barker; PJ Bremer (New Zealand Journal of Marine and Freshwater Research, 2012)
The influence of season, gender and sexual maturity on the biochemical composition (moisture, protein, total lipids, triglycerides, cholesterol, phospholipids, free amino acids, glucose and glycogen) of gonads from the endemic New Zealand sea urchin Evechinus chloroticus was investigated. Gonads were obtained from urchins during the austral autumn, winter, summer and spring, over a 23‐month period. Biochemical differences between genders were less pronounced in autumn (March to May) and winter (June to August) when more nutritive cells were present in the gonads, and more distinct over spring (September to November) and summer (December to February) months as the gametogenic cells matured, thus highlighting the importance of assessing testes and ovaries separately during biochemical analysis. Differences in the biochemical composition of testes and ovaries were the least pronounced during autumn, which suggests this will be the best season to harvest E. chloroticus in order to enhance taste and flavour, and reduce variability.

Age verification, growth and life history of rubyfish Plagiogeneion rubiginosum - PL Horn; HL Neil; LJ Paul; PJ McMillan (New Zealand Journal of Marine and Freshwater Research, 2012)
Age verification of rubyfish ( Plagiogeneion rubiginosum ) was sought using the bomb radiocarbon chronometer procedure. Stable isotopes were investigated for life history characteristics. Radiocarbon ( 14 C) and stable isotope (δ 18 O and δ 13 C) levels were measured in micro‐samples from five otoliths that had been aged using a zone count method. All the core 14 C measurements were ‘pre‐bomb’ indicating ages of at least 45 years, and the 14 C measurements across the otolith sections suggested that the zone‐count ageing method described herein is not biased. Maximum estimated age was 100 years. There was no significant between‐sex difference in the von Bertalanffy growth curves. The δ 18 O values indicated that rubyfish are near‐surface as juveniles, and move deeper with age. Adults appear to reside in 600–1000 m; this is deeper than most trawl‐capture data suggest, but not implausible, and has stock assessment implications. The δ 13 C values reflect fish metabolic rates, trophic feeding levels and oceanographic conditions. The stable isotopes record the environmental life history of each fish, and have value in distinguishing stocks and/or indicating vertical and latitudinal migratory patterns.

Effects of environmental gradients on the distribution of harpacticoid copepods in an intertidal flat, Portobello Bay, Otago Harbour, New Zealand - TJ Stringer; JC Korsman; G Peralta; V Keesing; LA Tremblay; CN Glover (New Zealand Journal of Marine and Freshwater Research, 2012)
Harpacticoid copepods are often one of the most dominant taxa in marine sediments, but there is limited knowledge of the physicochemical sediment characteristics that affect distribution of native New Zealand copepod species. Environmental gradients and abundance of harpacticoid copepods were therefore surveyed in Portobello Bay, an intertidal sand and mud flat in Otago Harbour, New Zealand. Generalised linear mixed models (GLMMs) were used to determine the relationship between physical factors and species abundance as well as to examine interspecies interactions. Six copepod species were present at the study site: Amphiascoides sp. , Enhydrosoma sp., Parastenhelia megarostrum , Robertsonia propinqua , and two species of Quinquelaophonte . Distribution of species was found to be significantly correlated to sediment size, organic content, tidal reach, salinity and pH. In addition to these physical factors, species–species interactions also affected copepod abundance. This information is relevant for understanding factors influencing copepod distribution, but also will shape guidelines for use in marine sediment bioassays using harpacticoid copepods.

Acid Mine Drainage Index (AMDI): a benthic invertebrate biotic index for assessing coal mining impacts in New Zealand streams - DP Gray; JS Harding (New Zealand Journal of Marine and Freshwater Research, 2012)
Acid mine drainage (AMD) is a widespread phenomenon globally. Drainage into streams from coal mines often contains a cocktail of acidic waters high in dissolved metals, and consequently stream invertebrate communities may be severely impacted. Traditionally, the intensity of impacts has been assessed by combinations of water chemistry and benthic invertebrate metrics; however, a metric specifically designed for assessing mining impacts has not been developed. We propose a benthic invertebrate biotic index: the Acid Mine Drainage Index (AMDI), based on species presence data. The AMDI has been developed by associating water chemistry and benthic invertebrate community data collected from 91 sites. AMD indicator scores for 57 taxa were calculated using weighted averaging. Site scores can range from 0 (severely impacted) to 100 (unimpacted) and sites can be categorised as ‘severely impacted’, ‘impacted’ or ‘unimpacted’. Comparisons between AMDI and traditional indices indicated the AMDI is more accurate at detecting mine drainage.

Use of bacterial communities to assess the ecological health of a recently restored stream - G Lear; P‐Y Ancion; J Harding; GD Lewis (New Zealand Journal of Marine and Freshwater Research, 2012)
We assess the utility of bacterial community data for providing an indication of stream health in a recently ‘restored’ urban stream. A community DNA fingerprinting technique was used to characterise the bacterial community within Okeover Stream, and a lesser impacted, nearby stream. No significant differences in bacterial community structure were detected between streams. However, further investigation revealed highly elevated levels of Zn, Pb and Cu associated with microbial biofilms in Okeover Stream and an increased abundance of genes encoding for bacterial resistance to Co, Zn and Cd. Benthic invertebrates were also sampled, confirming that despite recent attempts at stream restoration, the ecological health of the Okeover Stream remains poor. While the analysis of macroinvertebrate communities appeared to provide a more informative measure of overall stream health, we show that the targeted analysis of bacterial functional genes can be used to identify possible causes of declining ecological health.

Macrofaunal colonisation of stranded Durvillaea antarctica on a southern New Zealand exposed sandy beach - C Dufour; PK Probert; C Savage (New Zealand Journal of Marine and Freshwater Research, 2012)
Samples of the kelp Durvillaea antarctica were placed in mesh bags on the upper shore of a southern New Zealand exposed sandy beach and monitored over 30 days to examine their decomposition and macrofaunal colonisation. Amphipoda, Staphylinidae, other Coleoptera and Diptera made up 99.9% of total macrofaunal abundance and biomass of the colonising fauna. Amphipoda and Staphylinidae abundance differed significantly between days of exposure. All main taxonomic groups, except other Coleoptera, differed in biomass between days of exposure and between seasons, with greater biomass in autumn than winter. Decomposition rate and moisture content of D . antarctica differed significantly between days of exposure and between seasons, whereas carbon content only differed significantly over time. Correlations between macrofaunal abundance and the decomposition rate, and total macrofaunal abundance and the C:N ratio, suggest that the macrofaunal community prefers older wrack, despite it being lower in nitrogen content then fresh kelp.

Ikawai: freshwater fishes in Māori culture and economy - BJ Hicks; EM Watene‐Rawiri (New Zealand Journal of Marine and Freshwater Research, 2012)

Factors affecting farmers’ adoption of integrated rice–fish farming systems in the Mekong delta, Vietnam - Roel H. Bosma; Dang K. Nhan; Henk M. J. Udo; Uzay Kaymak (Reviews in Aquaculture, 2012)
This study investigated the determinants of the adoption of improved rice–fish farming systems in the Mekong delta to support policy making, agricultural land‐use planning and extension of integrated rice–fish farming. Recently these systems have been referred to as adaptations to climate change, while traditional rice–fish systems have often been abandoned. In 2006, we carried out surveys among 94 farmers either practising rice monoculture or having an improved rice–fish system. We analysed data among others with binary logistic regression and simulated adoption by using fuzzy logic. Per capita and per hectare incomes of households practising rice–fish systems were nearly double, while their farm size was 1.3 times larger than that of the rice monoculture farms. Households with larger homesteads, i.e. neighbouring irrigated fields and ponds, better access to financial capital and more know‐how of rice and fish culture and their integration, were more likely to adopt rice–fish systems. Previously identified drivers and factors for adoption, such as an appropriate agro‐ecological context and the farmer’s education and training level, were confirmed. Promoting rice–fish systems needs participatory extension and research approaches for sustainable agriculture strategies such as integrated pest management (IPM) in which farmers, trainers and researchers optimize technologies in constantly changing contexts.

Chinese Abstracts (Reviews in Aquaculture, 2012)

Impact of climate change in Mediterranean aquaculture - Rui Rosa; António Marques; Maria L. Nunes (Reviews in Aquaculture, 2012)
The Mediterranean Sea is the biggest marginal sea of the Earth and is at the centre of the life for several millions of people. Seafood is consumed widely in this region, with an average of 16.5 kg/capita/year, and one‐fourth of the seafood supply comes from aquaculture activities. The Mediterranean aquaculture sector has expanded in recent decades. Production increased by 77% over the past decade reaching about 1.3 million metric tonnes in 2009. The total value of production was around 3700 million US dollars, representing 3.4% of the value of global aquaculture production. The growth of seafood demand in the Mediterranean is expected to increase in the future, especially in southern countries. Yet, during the 21st century, the Mediterranean basin is expected to observe: (i) an increase in air temperature of between 2.2°C and 5.1°C; (ii) a decrease in rainfall of between 4% and 27%; (iii) an increase in drought periods related to a high frequency of days during which the temperature would exceed 30°C; and (iv) an increase of the sea level of around 35 cm and saline intrusion. Moreover, extreme events, such as heat waves, droughts or floods, are likely to be more frequent and violent. This paper reviews the present status of Mediterranean aquaculture (e.g. production trends, main farmed species, production systems, major producing countries), the most relevant impacts of climate change on this sector (temperature, eutrophication, harmful algae blooms, water stress, sea level rise, acidification and diseases) and proposes a wide range of adaptation and mitigation strategies that might be implemented to minimize impacts.

Directive 2010/63/EU on animal welfare: a review on the existing scientific knowledge and implications in cephalopod aquaculture research - António V. Sykes; Filipa D. Baptista; Rui A. Gonçalves; José P. Andrade (Reviews in Aquaculture, 2012)
This review intends to provide a reflection regarding Directive 2010/63/EU, on animal welfare, and its application concerning cephalopod breeding and experimentation in aquaculture research. To do so, we gathered different perspectives of our group members, involving two cephalopod aquaculture researchers, an aquaculture fish production technician and a veterinary professional, the latter with no background on cephalopod research. The inclusion of this class in the animal welfare legislation; the definition of live cephalopods, stress, pain and suffering are revised according to the latest scientific knowledge. Considering the 15 year background that the Centre of Marine Sciences holds on the cultivation of the European cuttlefish, an evaluation of existing production protocols, aquaculture technology related research, ethics and cephalopod welfare are discussed. The application of anaesthesia, analgesia and euthanasia is discussed, bearing in mind the different procedures applied on a daily basis in aquaculture breeding and experimentation and the requirements of the new Directive. Finally, an overview of the above and progress on 3Rs (replacement of animals, reduction in number of animals and refinement of procedures) application to cephalopod welfare is presented.

Exploitation and conservation of fish genetic resources in Africa: issues and priorities for aquaculture development and research - Curtis E. Lind; Randall E. Brummett; Raul W. Ponzoni (Reviews in Aquaculture, 2012)
Africa harbours a rich biological diversity of native fish resources. Recognition of the potential to use these resources to make significant contributions towards improving African food security through aquaculture has existed for some time. A key challenge, however, is achieving compatibility between the two urgent, but sometimes conflicting, goals of reducing poverty and food insecurity in Africa through aquaculture development while paying due attention to the conservation of natural biodiversity and fish genetic resources (FiGR). In this paper we highlight the overarching challenges concerning the conservation and exploitation of FiGR for the long‐term development of aquaculture for food production in Africa. We address the major issues requiring attention in genetic improvement programs in order to take full advantage of the highly diverse wild FiGR in Africa, and we expand on strategies such as zoning, environmental risk analysis and molecular characterization approaches that can be used to minimize the potential harm to wild FiGR arising from aquaculture activities and future development. Finally, we discuss the challenge of strengthening local capacity. The enhancement of local capacity is essential because it will enable the fundamental link required to achieve the desired outcome of increasing the productivity of aquatic animals for food in Africa in a sustainable manner. We trust that this paper will provide a good basis for an in‐depth discussion of the subject, as well as guidance on future research and development priorities for the compatible exploitation and conservation of FiGR in Africa.

Issue Information (Reviews in Aquaculture, 2012)

Occurrence of the marine yellow‐green algae Vaucheria velutina C. Agardh and Vaucheria longicaulis Hoppaugh (Xanthophyceae: Vaucheriaceae) in Auckland, New Zealand - MD Wilcox (New Zealand Journal of Marine and Freshwater Research, 2012)
The yellow‐green algae Vaucheria velutina and Vaucheria longicaulis are identified using morphological characters of fertile material from the eastern coastline of Auckland. The former species occurs in extensive low intertidal beds on sheltered, muddy shores. The latter species was found in Orakei Basin, and is a new record for New Zealand.

Diffuse contributions dominate over point sources of soluble nutrients in two sub‐catchments of the Manawatu River, New Zealand - JKF Roygard; KJ McArthur; ME Clark (New Zealand Journal of Marine and Freshwater Research, 2012)
Nitrogen and phosphorus concentrations in the Manawatu River, New Zealand, are among the highest nationally. To target policies to address these nutrient levels effectively, this study sought information on relative contributions of soluble nutrients from point and diffuse (non‐point) sources at various river flows and in relation to concentration‐based regulatory targets using load calculations. In the upper Manawatu and Mangatainoka sub‐catchments of the Manawatu River, measured nutrient loads were 55–154% greater than target nutrient loads. Measured loads were predominately from diffuse sources, which contributed 98% or more of the soluble inorganic nitrogen (SIN) and 84–88% of the dissolved reactive phosphorus (DRP) at all flows. At low flows, point source inputs contributed up to 64% of the DRP in the upper Manawatu sub‐catchment. This study suggests policy to manage nutrient enrichment in these areas should target inputs from diffuse sources at all flows, along with management of point sources at low flows.

Nitrogen fate and transport in a watercress‐dominated stream - TJ Cox; JC Rutherford (New Zealand Journal of Marine and Freshwater Research, 2012)
A combination of numerical modelling and field and mesocosm experiments were used to quantify the impacts of watercress stands on nitrogen dynamics in a small New Zealand stream. A series of tracer releases, supported by numerical modelling, were performed to a reach dominated by watercress and then to the same reach cleared of watercress. Results show watercress to be dominating in‐stream nitrogen processing through both rapid uptake and hydraulic impacts. A 6–11% loss of N mass was measured over a 100‐m reach with watercress present, whereas no loss of N mass was measured over the same reach cleared of watercress. Transient storage was approximately four times larger with watercress present compared with the same reach without the plants. Model parameterisation was supported by a series of ex situ mesocosm experiments that quantified biomass‐specific uptake rates (1–2.5 mg‐N/g/day) for two different growth stages. These experiments also revealed a lack of coupling of uptake rates with measured photosynthesis rates, contrary to many past modelling approaches.

Is bull‐kelp kelp? The role of common names in science - CI Fraser (New Zealand Journal of Marine and Freshwater Research, 2012)
Common names are non‐specific by definition, and scientists should naturally avoid placing strict rules on their usage. There are many examples of common names applying to numerous, often only distantly related taxa, yet the term ‘kelp’ is increasingly being used to refer solely to members of the macroalgal order Laminariales, and some scientists now assert that any other use is incorrect. A brief examination of the word's etymology, however, demonstrates that kelp can with equal validity also refer to non‐laminarialean taxa. Many people do still use the word ‘kelp’ in its broader sense, and these conflicting definitions of the word can lead to confusion and miscommunication between scientists and the general public. This review demonstrates that the definition of ‘kelp’ should remain relaxed, in accordance with its role as a common name.

Water quality and benthic macroinvertebrate communities in karst landscapes of North Island, New Zealand: influences of water sources, habitat type and anthropogenic disturbances - DJ Reid; MR Scarsbrook; AE Wright‐Stow; KSS van Houte‐Howes; K Joy (New Zealand Journal of Marine and Freshwater Research, 2012)
In karst landscapes, aquatic habitats differ in terms of the relative contributions of different water sources (allogenic surface stream vs autogenic karst groundwater) and their geomorphology. Benthic macroinvertebrate community structure in these habitats is likely to vary in response to this heterogeneity, as well as to the physicochemical differences between water flowing through pasture vs native forest dominated catchments. Surveys were conducted to examine the influences of water source, habitat type (main stream‐ways and side passages in caves, and epigean springs) and surrounding land use (native forest or pasture) on the water quality and benthic community structure in the Maniapoto Karst, North Island, New Zealand. Generally, springs and cave side passages received more autogenic water, indicated by lower temperatures and higher conductivities, than the main stream‐ways of caves. However, in terms of community structure, the epigean springs and cave side passages were most distinct from each other, whilst the main stream‐ways of caves were intermediate between the other two habitats. Temperature and nitrate concentrations were higher in sites surrounded by pasture than those in native forest, but surrounding land use exerted less influence on macroinvertebrate community structure than habitat type. A comparison of community structure in caves with high and low tourist traffic failed to identify any significant effects.

The toxic effects of three dinoflagellate species from the genus Karenia on invertebrate larvae and finfish - F Shi; P McNabb; L Rhodes; P Holland; S Webb; J Adamson; A Immers; R Gooneratne; J Holland (New Zealand Journal of Marine and Freshwater Research, 2012)
Three species of Kareniaceae, Karenia brevis , Karenia brevisulcata and Karenia mikimotoi were assessed for toxicity to juvenile Chinook salmon ( Oncorhynchus tshawytscha ), snapper ( Pagrus auratus ) and six species of marine invertebrate larvae (Greenshell TM mussel, pacific oyster, paua [New Zealand abalone], sea slug, sea urchin and brine shrimp). Karenia brevis was ichthyotoxic to juvenile salmon with a LT 50 of 0.75 h at 0.18 × 10 6 cells L –1 but juvenile snapper were less sensitive (LT 50 of 4.5 h at 5.9 × 10 6 cells L –1 ). Karenia brevisulcata also showed differential toxicity to juvenile salmon and snapper with LT 50 of 0.48 h at 11 × 10 6 cells L –1 and 7.5 h at 16 × 10 6 cells L –1 respectively. However, no acute symptoms were observed in the fish following 48 h exposure to K. mikimotoi at 3.4 × 10 6 cells L –1 . Karenia brevis at the highest level tested (8.7 × 10 6 cells L –1 ) did not cause observable symptoms in any of the invertebrate larvae over 24 h. Karenia mikimotoi only affected paua larvae (LT 50 10 h at 12 × 10 6 cells L –1 ). Karenia brevisulcata was highly toxic to mussel, sea urchin and paua larvae (LT 50 1–6.1 h at 7.5–9.6 × 10 6 cells L –1 ), toxic to sea slug and oyster larvae (LT 50 6 h at 80 × 10 6 cells L –1 and 9.2 h at 34 × 10 6 cells L –1 respectively) but did not affect brine shrimp. Analysis of test cultures by liquid chromatography‐mass spectrometry confirmed that K. brevis produced brevetoxins (52 pg cell –1 ; mainly brevetoxin‐2). Karenia brevisulcata produced brevisulcatic acids (BSXs) and the more toxic Karenia brevisulcata toxins (KBTs). Karenia mikimotoi did not produce brevetoxin, BSXs or KBTs. The present study confirms the broad threats that blooms of K. brevisulcata pose to marine ecosystems and aquaculture, and the hazards of K. brevis to finfish and K. mikimotoi to abalone respectively.

Genetic diversity and population structure of the pot‐belly seahorse Hippocampus abdominalis in New Zealand - J Nickel; R Cursons (New Zealand Journal of Marine and Freshwater Research, 2012)
Genetic diversity and population structure of New Zealand populations of the pot‐belly seahorse Hippocampus abdominalis were explored via three mitochondrial DNA markers (814 bp of cytochrome b, 624 bp of cytochrome oxidase 1 and 404 bp of the control region) and four microsatellite loci (Habd3, Habd6, Habd7 and Habd9). These markers revealed between 0.7–2.2% sequence divergence and 32–46 alleles with low differentiation among populations around the coastline. In total, 169 seahorses (79 females and 90 males) were sampled with 36 sequences generated for each marker and 166 genotypes attained. It is hoped that this new knowledge will aid in the development of future conservation management.

Estimation of native fish density in lowland streams by repeated electric fishing during the day and following night - E Graynoth; M Bonnett; D Jellyman (New Zealand Journal of Marine and Freshwater Research, 2012)
Single reaches in three lowland streams in Canterbury, New Zealand, were enclosed with stop‐nets and fish removed by repeated electric fishing passes through the day and following night during base flow conditions in late summer. The proportion of fish caught in each pass varied between species and increased with fish size. Electric fishing efficiency declined in the second and third daytime passes, to 0.73 and 0.79 of the first pass respectively, but increased in the first and second night‐time passes to 1.87 and 2.02. Population estimates, based on the first two or three daytime passes, accounted for only 62% and 82% of the population estimated using all five day and night passes. A high percentage of small benthic species remained hidden within the substrate during the day but emerged at night and became more vulnerable to electric fishing. Single or multiple daytime passes can be used to estimate the approximate density of most native fish species and size classes in small lowland streams and rivers provided calculations take into account fish hidden within the substrate and marginal vegetation.

Investigating the fate of sodium monofluoroacetate during rain events using modelling and field studies - MS Srinivasan; A Suren; J Wech; J Schmidt (New Zealand Journal of Marine and Freshwater Research, 2012)
We examined catchment‐scale transport of sodium monofluoroacetate (‘1080’) in rainfall run‐off. We developed a hydrological model describing the overland transport of 1080 and validated model results using field data from a headwater catchment, where we intensively sampled a stream during a rainfall event (28 mm in 8 h) that followed 1080 aerial application. Only one stream sample contained a measurable concentration of 1080 (0.1 µg/l; collected 105 min from the start of rainfall), while 1080 was below detection limits (0.1 µg/l) in all other samples. Absence of visually observable overland flow conditions (puddles and saturated areas connected to the stream) early during the rainfall event suggested that overland transport might not have been the dominant mechanism in this catchment. Moreover, analyses of soilwater samples collected from lysimeters installed in the catchment indicated the propensity of 1080 to leach into soil, suggesting the need to investigate subsurface transport pathways.

A new tool for visualising multi‐dimensional datasets: an example of fish schools around artificial reefs - M Kang; T Nakamura; A Hamano (New Zealand Journal of Marine and Freshwater Research, 2012)
We demonstrated a tool for visualising multi‐dimensional datasets, using an example of fish schools around artificial reefs off the coast of Shimonoseki, Yamaguchi prefecture, Japan. The datasets included acoustic surveys of fish schools, water temperature data, descriptions of the artificial reefs, sediment data, and bathymetry and coastal line data. These datasets were integrated into geographic information system software, which can be used to describe the relationship between water temperature and fish schools; fish schools associated with reefs; and the status of the artificial reefs on the classified seabed. This new tool provides a better understanding of the distribution of fish schools based on their spatial location in context with environmental information around artificial reefs.

Chinese Abstracts (Reviews in Aquaculture, 2012)

Economically important production relationships in channel catfish ( Ictalurus punctatus ) foodfish production - Umesh Bastola; Carole R. Engle (Reviews in Aquaculture, 2012)
The catfish industry ( Ictalurus punctatus ), the largest segment of aquaculture in the USA, has declined in the number of operations, total yield and sales in recent years. This has led to a call for innovations to improve production efficiency and to lower the cost of production. This paper reviewed the literature on management parameters that affect economically important production parameters under the control of an individual catfish farmer. Stocking density, size of fish at stocking, duration of culture, cropping systems, feeding strategies and aeration were shown to significantly affect the economically important parameters of investment costs, yield and feed conversion ratio. Additional work is needed to quantitatively model the effects of multiple parameters and to develop user‐friendly versions to assist catfish farmers in decision making.

Effect of salinity on egg hatching, yolk sac absorption and larval rearing of Senegalese sole ( Solea senegalensis Kaup 1858) - Emilio A. Salas Leitón; Ana Rodriguez‐Rúa; Esther Asensio; Carlos Infante; Manuel Manchado; Catalina Fernández‐Díaz; José P. Cañavate (Reviews in Aquaculture, 2012)
Assays carried out under laboratory‐controlled conditions revealed that eggs of Senegalese sole, Solea senegalensis Kaup 1858, incubated at 10, 18, 27 and 33 grams per litre (g L −1 ) reached their maximum hatching rates (above 80%) 48 h after incubation. In contrast, hatching was significantly delayed (24 h) and completely failed when the salinity was set at 5 and 0 g L −1 , respectively. Newly hatched and early‐developing yolk sac larvae presented similar survival rates 3 days after hatching (DAH) when exposed to salinities of 10, 18, 27 and 33 g L −1 . Larvae incubated at 5 g L −1 salinity died a few hours after hatching once they were released from their respective chorions. The notochord length was unmodified by salinity 5 DAH. Nevertheless, an overall lower myotomal height and a putative delay in the depletion of yolk sac were found in larvae reared at 10 g L −1 . This anomaly in overall larval development became more pronounced with the occurrence (100% of analysed larvae) of mouth deformities and a lack of functionality under 10 g L −1 salinity. Transferring 2 DAH larvae from 33 g L −1 (exhibiting normal mouth development) to a medium with a salinity of 10 g L −1 had no effect on first feeding, weight and metamorphic index. Overall our results indicate the existence of a key time window (0–2 DAH) in which a salinity value higher than 10 g L −1 is required to achieve adequate mouth development and further functionality of larvae. The present work represents a valuable contribution to the sole industry, opening new possibilities in hatchery management practices.

Use of chemicals and biological products in Asian aquaculture and their potential environmental risks: a critical review - Andreu Rico; Kriengkrai Satapornvanit; Mohammad M. Haque; Jiang Min; Phuong T. Nguyen; Trevor C. Telfer; Paul J. van den Brink (Reviews in Aquaculture, 2012)
Over the past few decades, Asian aquaculture production has intensified rapidly through the adoption of technological advances, and the use of a wide array of chemical and biological products to control sediment and water quality and to treat and prevent disease outbreaks. The use of chemicals in aquaculture farms has raised environmental concerns owing to their potential impacts on downstream aquatic ecosystems. Currently little is known about the environmental fate and effects of the chemicals used in Asian aquaculture. Consequently, we reviewed recent information on the use of chemical and biological products in the most important Asian aquaculture producing countries and briefly summarize their main potential environmental impacts. We provide an overview of the main factors controlling the use of these chemicals and describe the international risk assessment guidelines available for aquaculture chemicals. Finally, data gaps and research needs for their implementation in Asian countries are discussed. Our review aims to form a basis for developing environmental risk assessment studies of the chemicals used in Asian aquaculture.

Pathogenesis, virulence factors and virulence regulation of vibrios belonging to the Harveyi clade - Hettipala Arachchige Darshanee Ruwandeepika; Thotawaththage Sanjeewa Prasad Jayaweera; Patit Paban Bhowmick; Indrani Karunasagar; Peter Bossier; Tom Defoirdt (Reviews in Aquaculture, 2012)
The Harveyi clade or core group of the Vibrio genus includes both pathogenic and non‐pathogenic bacteria. Some of the species belonging to the clade, such as Vibrio harveyi , Vibrio alginolyticus , Vibrio campbellii and Vibrio parahaemolyticus , include serious pathogens of aquatic organisms. Importantly, within these species, some strains are pathogenic, whereas others are not. Other members of the clade, such as Vibrio natriegens and Vibrio mytili are reported to be non‐pathogenic. As bacteria belonging to the Harveyi clade show a high diversity with respect to virulence and as the virulent members cause high mortalities in the aquaculture sector, it is important to understand which gene products are responsible for the pathogenicity of the bacteria and how expression of these virulence factors is regulated. This knowledge will ultimately allow for the development of biocontrol measures that aim to reduce the severe losses that are currently faced in the aquaculture sector as a result of vibriosis. In this review, we discuss the pathogenesis of bacteria belonging to the Harveyi clade, their impact on the aquaculture sector, the virulence factors that are involved in pathogenicity and their regulation.

Interspecific fish hybrids in Brazil: management of genetic resources for sustainable use - Diogo T. Hashimoto; José A. Senhorini; Fausto Foresti; Fábio Porto‐Foresti (Reviews in Aquaculture, 2012)
Serrasalmid and pimelodid fish hybrids represent important advances for aquaculture in Brazil, but they also constitute serious genetic risks to cultivated and natural populations. Serrasalmid hybrids (‘tambacu’, ‘tambatinga’ and ‘patinga’) result from crosses between Colossoma macropomum , Piaractus mesopotamicus and Piaractus brachypomus . Pimelodid hybrids (‘ponto e vírgula’, ‘cachandiá’ and ‘cachapira’) arise from crosses between Pseudoplatystoma corruscans , Pseudoplatystoma reticulatum , Phractocephalus hemioliopterus and Leiarius marmoratus . The problems associated with hybrids mainly result from inappropriate use because these animals are reproductively compatible with their parental species. This review shows that monitoring of fish hybrids using genetic techniques is necessary for their sustainable development in aquaculture. The genetic technologies used to identify fish hybrids include cytogenetic methods, which are considered to be low cost, and polymerase chain reaction‐based molecular markers, which are associated with high throughput. Therefore, both types of genetic methodologies should be applied in monitoring programs aimed at brood stock management, wild stocks, the trade of hybrid juveniles and processed fish products in markets. Moreover, physical and genetic confinement of hybrids in aquaculture operations will be necessary to avoid the problems posed by these animals. The expected result of these measures will be the production of genetically improved animals by fish farms, allowing the sector to develop further and offering high‐quality animal protein.

Issue Information (Reviews in Aquaculture, 2012)

Unusual stability of diet of the New Zealand fur seal ( Arctocephalus forsteri ) at Banks Peninsula, New Zealand - LL Allum; FW Maddigan (New Zealand Journal of Marine and Freshwater Research, 2012)
The diet of the New Zealand fur seal Arctocephalus forsteri was determined from examination of scats and regurgitates collected from two breeding colonies at Banks Peninsula, Canterbury. Identifiable otoliths and squid beaks were obtained from 392 scats and 16 regurgitations collected over four seasons in 2008. Nine species were identified in scats and three species were identified in regurgitates. Arrow squid ( Nototodarus sloanii ) accounted for the greatest proportion of biomass taken (>90%), followed by lanternfish ( Lampanyctodes hectoris and Symbolophorus sp . ; 4%) and barracouta ( Thyrsites atun ; 2.6%). Although slight differences in diet were detected spatially and temporally, both colonies had a squid‐dominated diet year round. This differs from the seasonal dietary variation shown in other areas around mainland New Zealand.

Editorial Report 2011 - Doug Mountfort (New Zealand Journal of Marine and Freshwater Research, 2012)

Application of tyramide signal amplification‐fluorescence in situ hybridisation and flow cytometry to detection of Heterosigma akashiwo (Raphidophyceae) in natural waters - J Lee; T Katano; M Chang; M‐S Han (New Zealand Journal of Marine and Freshwater Research, 2012)
We developed protocols to analyse the cell cycle of Heterosigma akashiwo in the natural phytoplankton assemblage using tyramide signal amplification‐fluorescence in situ hybridisation (TSA‐FISH) and flow cytometry. We determined the optimum probe and formamide concentrations for the species‐specific TSA‐FISH probe to be 0.5 ng µL −1 and 40%, respectively. The probe did not hybridise to non‐target phytoplankton including Chattonella sp., which is closely related to Heterosigma and has high sequence similarity to it. We could successfully identify G1‐ and G2‐phase cells and the diel cell cycle of H. akashiwo not only in the laboratory but also in the field after TSA‐FISH. These results demonstrate that TSA‐FISH for H. akashiwo in natural coastal waters could serve as a powerful tool for understanding their bloom mechanism using flow cytometry.

The Kapiti Marine Reserve (New Zealand): spatial and temporal comparisons of multi‐species responses after 8 years of protection - A Pande; JPA Gardner (New Zealand Journal of Marine and Freshwater Research, 2012)
Kapiti Marine Reserve (KMR) was established in May 1992 following a single baseline biological survey. We surveyed macroalgal, macroinvertebrate and fish species for abundance and/or size at two sites inside and two outside KMR and then conducted reservation status (inside vs outside KMR) and temporal (1992 baseline vs 1999–2000) tests to quantify biological responses after 8 years of protection. Reservation status has had a significant effect on abundance or size for four fish species (banded wrasse, blue cod, butterfish, blue moki), but not for heavily fished macroinvertebrates (two species of paua, kina, rock lobster). Temporal analyses revealed only one significant difference (banded wrasse), but that is not attributable to the reserve. Despite low statistical power to detect change, the value of the baseline survey is highlighted by our ability to understand and interpret better the biological responses that we observed and to demonstrate conservation outcomes at KMR.

Autumn diet of recolonising female New Zealand sea lions based at Otago Peninsula, South Island, New Zealand - AA Augé; C Lalas; LS Davis; BL Chilvers (New Zealand Journal of Marine and Freshwater Research, 2012)
New Zealand (NZ) sea lions ( Phocarctos hookeri ) are slowly recolonising the Otago coast, South Island, New Zealand. The increase in their numbers may lead to resource competition with other marine predators and fisheries. We determined the diet of female NZ sea lions at Otago during autumn. In total, 571 scats and 110 regurgitations were collected on Otago Peninsula during 2008 and 2009. Barracouta ( Thyrsites atun ) and jack mackerel ( Trachurus sp.) were the two main prey species and accounted for 26% and 31% of the reconstituted biomass, respectively. This was consistent between two years. Only five other species contributed > 5% of the diet by biomass in either year. Prey species are all found on the narrow continental shelf surrounding Otago Peninsula. The main prey species of Otago NZ sea lions may be of higher energy content than prey in the Auckland Islands (remnant breeding area). Resource overlap with other marine predators and fisheries appears to occur around Otago Peninsula. A marine trophic model of the area off Otago Peninsula would help understanding potential competition between marine predators and fisheries in this area.

Survival potential of autotrophic phytoplankton species collected from ballast water in international commercial ships - SH Baek; SW Jung; MC Jang; B Hyun; K Shin (New Zealand Journal of Marine and Freshwater Research, 2012)
To understand the impact of environmental factors on the survival success of introduced species by ship ballast water, we investigated the survival potential of autotrophic phytoplankton from international commercial ships. Ballast water was collected from chemical tankers that originated in three different bioregions. A laboratory experiment was designed to simulate the resource‐limited waters of the ballast tank as well as the eutrophic water of port and coastal waters in which nutrients are plentiful. Phytoplankton survival and population growth were significantly higher in nutrient‐enriched water than in water from the shipside or ballast water. In particular, the centric diatom Thalassiosira pseudonana was able to tolerate a wide range of salinities (0–30 PSU) and its high survival potential indicated that it could colonise novel ecosystems successfully.

Growth, behaviour and colour changes of juvenile King George whiting ( Sillaginodes punctata ) mediated by light intensities - CA Meakin; JG Qin (New Zealand Journal of Marine and Freshwater Research, 2012)
Light is an important environmental factor regulating physiological processes and ecological activities in fishes. This research aimed to examine the effect of light on the growth, distribution and body colour of juvenile King George whiting ( Sillaginodes punctata ) when fish were exposed to different light levels under laboratory conditions. In this study, the fish were exposed to three light levels (25, 500, and 1000 lux) in triplicate for two months. Comparisons were made for growth, body colour and behavioural changes between treatments. During the experimental period, there were no statistical differences in specific growth rate, survival, growth efficiency and condition factor between the light levels. Although light did not affect swimming speed or encounter rates, it did influence group flight activity and fish distribution in the tanks. Whiting in low light preferred to spend more time grouped at the bottom of the tank than at medium (500 lux) or high light (1000 lux). Likewise, after having been exposed to low light, whiting exhibited a brighter colour and had fewer body markings and counter‐shading than fish in medium and high light intensities. Differences in fish distribution and body colour between medium and high light intensities were not detected. This study offers a new insight into understanding the impact of light on behaviour and body colour of fish, which may contribute to the spatial distribution, predator avoidance and recruitment of fish in inshore coastal waters.

Assessment of a major shore‐based marine recreational fishery in the southwest Atlantic, Argentina - FM Llompart; DC Colautti; CRM Baigún (New Zealand Journal of Marine and Freshwater Research, 2012)
This work provides, based on data from roving creel surveys, the first quantitative analysis for a main recreational fishery of the southwestern Atlantic coast. Anglers interviewed were willing to accept minimum size limits but mostly did not approve the maximum daily catch, despite the fact that they considered that the fishery quality was decreasing. Angler profile differed among months but the avidity effect was negligible. Fishing effort was highest during January, with the greatest total catch per unit effort (CPUE) in November and the highest total catch in December. Twelve species were caught, with Cynoscion guatucupa and Micropogonias furnieri accounting for 80% of the harvest. The average lengths for both species were larger than their size at first maturity. Mean (±SD) CPUE values (1.28±0.59 fish/angler/h) and total harvest were high compared with those of other recreational fisheries in the Southern Hemisphere. Some specific fishing‐management guidelines are proposed to promote good angling practices and sustainable long‐term use of the resource.

Short‐term reactions and long‐term responses of bottlenose dolphins ( Tursiops truncatus ) to remote biopsy sampling - G Tezanos‐Pinto; CS Baker (New Zealand Journal of Marine and Freshwater Research, 2012)
We analyse short‐term individual and group behavioural reactions and long‐term individual responses of bottlenose dolphins ( Tursiops truncatus ) in New Zealand to remote skin biopsy sampling. The biopsy system employed uses a small stainless steel tip (5‐mm diameter, 9‐mm length) mounted on a lightweight polycarbonate projectile, fired from a modified veterinary rifle with adjustable pressure. Individual and group behavioural reactions were scored on a 5‐point scale from 0 (no reaction) to 5 (strenuous reaction). A total of 187 individual and 145 group behavioural reactions were recorded from the Bay of Islands subpopulation, while 38 individual and 39 group behavioural reactions were recorded from the Doubtful Sound subpopulation. Short‐term reactions (

Phylogenetic analyses of bacteria in sea ice at Cape Hallett, Antarctica - EW Maas; AM Simpson; A Martin; S Thompson; EY Koh; SK Davy; KG Ryan; RF O'Toole (New Zealand Journal of Marine and Freshwater Research, 2012)
Every year, an area of sea ice forms around the continent of Antarctica that is inhabited by communities of microbes. Although the microbial component of this habitat has been postulated to play an ecologically important role in the Southern Ocean, our understanding of the diversity of Antarctic sea‐ice bacteria is limited. The aim of this study was to identify bacterial components present in sea ice at Cape Hallett. Total community DNA was isolated from sea‐ice cores and the 16S ribosomal RNA genes were amplified by polymerase chain reaction (PCR) using a range of universal and targeted primer sets. PCR products were de‐replicated using restriction fragment length polymorphism (RFLP) and distinct RFLP types were sequenced. The major bacterial classes identified consisted of α‐proteobacteria, γ‐proteobacteria, Cytophaga–Flavobacteria–Bacteroides group and a small number of Gram‐positive species. Our findings indicate that the bacterial component of sea ice at Cape Hallett is primarily heterotrophic. Cyanobacteria and Archaea were not detected using the methods and primer sets employed in this study. However, bacteria whose 16S rDNA sequences cluster with species that encode phototrophic genes were detected in our sea‐ice samples. This raised the possibility that bacterial phototrophy may occur in Antarctic sea ice.

Ontogenetic diet shifts in snapper ( Pagrus auratus : Sparidae) within a New Zealand estuary - NR Usmar (New Zealand Journal of Marine and Freshwater Research, 2012)
The diet of the sparid fish Pagrus auratus (snapper) was examined within the Mahurangi Harbour in north‐eastern New Zealand. Ontogenetic shifts occurred in diet. Individuals 100 mm consumed brachyuran crabs, caridean shrimps, bivalves, polychaetes and hermit crabs, with individuals >300 mm also able to consume harder shelled molluscs and bivalves. The stomach contents of juvenile snapper (10–100 mm) sampled across habitats of sand, shell hash, horse mussels and subtidal mud showed differences in major prey taxa; however, these differences were small. This may be advantageous for juveniles, which can then select a habitat for other qualities. A comparison with eight other studies on the diet of snapper from coastal areas showed crustaceans were consistently the most highly ranked major taxon; however, differences among other major taxa were relatively minor.

The influence of Tucetona laticostata (Bivalvia: Glycymeridae) shells and rhodolith patches on benthic‐invertebrate assemblages in Hauraki Gulf, New Zealand - SEA Dewas; S O'Shea (New Zealand Journal of Marine and Freshwater Research, 2012)
The large dog cockle, Tucetona laticostata (Quoy and Gaimard, 1835), is widely but sporadically distributed throughout coastal waters of Hauraki Gulf. One location at which this species proves common is around Otata Island, one of a series of islands in the ‘Noises’ complex in Hauraki Gulf, where it resides partially buried in gravel and rhodoliths in shallow water, at 5–15 m depth. The shells of T . laticostata collect in large post‐mortem deposits in an area ramping from the sea bed off southwestern Otata Island. Seasonal variation in and benthic macroinvertebrate composition of taxon assemblages within and outside T . laticostata /rhodolith mounds and gravel are described. Both benthic invertebrate mean taxon richness and abundance within T . laticostata /rhodolith habitat are higher than in gravel; spatial and temporal variation in these communities is reported. Anthropogenic threats to structurally complex T . laticostata shell and rhodolith‐based biogenic substrata are discussed.

List of Reviewers 2008–2011 (Reviews in Aquaculture, 2012)

The role of the brain in farmed fish - Sofronios E. Papoutsoglou (Reviews in Aquaculture, 2012)
As is well known, optimal levels of both homeostasis and welfare of farmed fish are almost completely dependent upon human endeavour to investigate fish brain capacities and utilize them for the greatest benefit. According to the accumulated research experience specifically concerning minimization of farmed fish stress, the final outcome of the involved mechanisms is strongly associated with fish species and biological stage as well as a number of rearing environment parameters related to the type of the production system applied. Based on the conclusions gained, it is clear that the fish brain‐neuroendocrinological system is an extraordinarily rich and expressive one forming a species‐specific living ethology that incorporates cognitive behaviour and ‘demands’, the whole constituting, in effect, the fish “personality”. The diverse facets of this ‘personality’ are expressed via a wide range of phenomena: e.g. the power of learning, memorizing, sound production, particular external coloration changes, courtship behaviour, parent care and “emotional feelings” including the manifestation of aggressiveness and the demonstration of “happiness”. The final conclusion to be drawn is that fish are indeed amazing creatures. One can only marvel at the superb plasticity of their brain which, over hundreds of millions of years and through myriad genomic, evolutionary and epigenetic developments, has enabled them to adapt and respond to and remarkably thrive in all extremes of environments, and all this though they lack a cerebral neocortex.

Experiments on an integrated aquaculture system (seaweeds and marine fish) on the Red Sea coast of Saudi Arabia: efficiency comparison of two local seaweed species for nutrient biofiltration and production - Yousef S. Al‐Hafedh; Aftab Alam; Alejandro H. Buschmann; Kevin M. Fitzsimmons (Reviews in Aquaculture, 2012)
Seaweeds absorb inorganic nutrient wastes from mariculture and reduce their undesirable environmental effects. Mariculture in Saudi Arabia is increasing rapidly, thus, to exploit aquaculture wastes and to reduce coastal pollution risks, local seaweeds were cultured using mariculture effluents in integration on the Red Sea coast. The aim of the present study was to test integrated aquaculture of seaweed and marine fish ( Oreochromis spilurus ) for the first time in Saudi Arabia and to determine the seaweeds, Ulva lactuca and Gracilaria arcuata , biomass production and inorganic nutrient bioremediation capabilities. Results showed that G. arcuata grew at a significantly higher rate (2.71% wet weight day −1 ) than U. lactuca (1.77% wet weight day −1 ). The biomass yield (42.38 g wet weight m −2 day −1 ) and net yield (91.11 g wet weight day −1 ) of G. arcuata were also significantly higher than U. lactuca (27.39 g wet weight m −2 day −1 and 58.89 g wet weight day −1 , respectively). Gracilaria arcuata removed 0.45 g m −2 day −1 of total ammonia nitrogen (TAN) with 80.15% removal efficiency and 1.03 g m −2 day −1 of soluble phosphate with 41.06% efficiency. Ulva lactuca removed 0.42 g m −2 day −1 of TAN with 83.06% removal efficiency and 1.07 g m −2 day −1 of soluble phosphate with 41.11% efficiency. Total tissue carbon of both species reached 25.1–26.9% and nitrogen content reached 3.0–3.2% of dry weight. The C/N ratio for both seaweeds was G. arcuata has relatively higher growth potential.

Proteomics: present and future in fish, shellfish and seafood - Xuxia Zhou; Yuting Ding; Yanbo Wang (Reviews in Aquaculture, 2012)
The aim of proteomics is to simultaneously resolve all potential proteins expressed by a cell, tissue or organism in a specific physiological condition. It will allow scientists to build and test better hypotheses, with the ultimate goal to find better solutions to challenges in agricultural sciences, medicine and environmental management. Recent and very promising applications of proteomics have also been provided in the field of aquaculture, such as the search for antigenic proteins, the detection of differentially regulated proteins and the characterization of biologically active proteins primarily to investigate the physiology, development biology and impact of contaminants in aquatic organisms. Thus, a brief overview of present classical proteomics methodology (electrophoresis and mass spectrometry) is presented, and the proteome technique will be focused in the context of applications beneficial to the field of fish, shellfish and seafood/seafood product. In addition, the future potential application and challenge of proteomics in aquaculture will also be discussed.

Three decades of horseshoe crab rearing: a review of conditions for captive growth and survival - Ruth H. Carmichael; Erik Brush (Reviews in Aquaculture, 2012)
Threats to wild horseshoe crab populations and growing interest in their use for research, education and biomedical applications have prompted demand for improved techniques to rear and maintain crabs in captivity. Although numerous laboratory studies have been conducted to determine growth and survival of horseshoe crabs under various conditions, these data have not been compiled and summarized to inform culture practices. We surveyed the literature and analysed the range of available techniques to identify and define a consistent set of conditions for maximum growth and survival of horseshoe crabs in culture. We considered three age classes; embryo, juvenile and adult, and included all extant species ( Limulus polyphemus , Carcinoscorpius rotundicauda , Tachypleus gigas and Tachypleus tridentatus ). We discovered relatively few published studies that clearly related husbandry conditions to growth and survival. Comparison among studies was complicated by inconsistent data collection and reporting techniques. Most published sources reported data for younger age classes, and more studies considered L. polyphemus than Asian species. The most commonly reported variables (temperature, salinity, enclosure maintenance and diet composition) showed size dependent and in some cases species‐specific effects on growth and survival that will be important in guiding culture efforts. We suggest that future studies give additional consideration to substrate type, water flow, dissolved oxygen concentrations, diet quality and the quantity and frequency of feeding. If laboratory‐reared stocks are to be used for propagation and restoration activities, future studies will benefit from closing these data gaps and promoting international data sharing.

Issue Information (Reviews in Aquaculture, 2012)

Chinese Abstracts (Reviews in Aquaculture, 2012)